The use of freeze-dry bovine pericardium in abdominal wall reconstructive surgery repair in dogs - Mohamed Yusof, Loqman; Wong, C. M.; G. G., Grace; Bejo, Mohd Hair; Abdul Rahman, Sheikh Omar; Abu Bakar @ Zakaria, Md Zuki; Yagoub Mohamed, Abdel Hafeez (Universiti Putra Malaysia Press, 2004)
This article describes the findings of macroscopic and microscopic evaluation abdominal wall surgery repair in dogs using freeze-dry bovine pericardium as a biomaterial.